Some characteristics of central metabolism in Acinetobacter sp. grown on ethanol - Pirog, Tatiana; Kuzminska, Yu. (My University, 2003)
Ethanol-grown cells of the mutant Acinetobacter sp. strain 1NG, incapable of producing exopolysaccharides, were analyzed for the activity of enzymes of the tricarboxylic acid (TCA) cycle and some biosynthetic pathways. In spite of the presence of both key enzymes (isocitrate lyase and malate synthase) of the glyoxylate cycle, these cells also contained all enzymes of the TCA cycle, which presumably serves biosynthetic functions. This was evident from the high activity of isocitrate dehydrogenase and glutamate dehydrogenase and the low activity of 2-oxoglutarate dehydrogenase. Pyruvate was formed in the reaction catalyzed by oxaloacetate decarboxylase, whereas phosphoenolpyruvate (PEP) was synthesized by the two key enzymes (PEP carboxykinase and PEP synthase) of gluconeogenesis. The ratio of these enzymes was different in the exponential and the stationary growth phases. The addition of the C4-dicarboxylic acid fumarate to the ethanolcontaining growth medium led to a 1.5- to 2-fold increase in the activity of enzymes of the glyoxylate cycle, as well as of fumarate hydratase, malate dehydrogenase, PEP synthase, and PEP carboxykinase (the activity of the latter enzyme increased by more than 7.5 times). The data obtained can be used to improve the biotechnology of production of microbial exopolysaccharide ethapolan on C2-substrates.
Keywords: ethanol metabolism; метаболизм этанола; tricarboxylic acid cycle; glyoxylate cycle; gluconeogenesis; biosynthesis; цикл трикарбоновых кислот; глиоксилатный цикл; глюконеогенез; биосинтез; метаболізм етанолу; цикл трикарбонових кислот; гліоксилатний цикл; глюконеогенез; біосинтез; кафедра біотехнології і мікробіології